Space Recycle between Theory and practice - Case study: Ministries square, Down Town - Bendary, Maya Atef; El-Gohary, Germin Farouk; Refai, Mohab AbdelMonem; Ibrahim, Karim Bayoumi (Journal of engineering sciences and information technology, 2023)
Egyptian cities are going through an integration process, while the new capital and other new areas are under constructions with the plan to construct other new cities to fight the overcrowded city centers and satisfy the intense need for homes and work opportunities in safer and better environment, lots of sites are evacuated leaving many untapped opportunities, some of those sites are in the center of the greater Cairo region. Such opportunities need to be studied and planned, need to be revived and turned into a point of attraction and investment, transforming such dying areas to high quality architecture adding a new spirt to the city while keeping the originality and identity of the region. After studying and analyzing methods and solutions used in international similar cases, taking human factor and residents need as the primary factor planning the solutions, while the area under study was analyzed, identifying the main reasons and residences needs, respecting the country development plan. Using the Space recycle methods and concepts as an adding tool to help reviving the dying areas and sites around Cairo, Space recycling methods or concepts can be the help needed to revive dying area in Cairo, it would offer a rebirth transforming dying sites into a vibrant development adding a new spirit to the city. Accordingly, and based on the analysis of the region and its requirements, guiding standards were set, while respecting the special nature of the heritage and archaeological buildings in the region.